Radioprotective Properties of Chitosan on Cultured Human Lymphocytes against Electron Beam Radiation - Shama Rao, Sukanya Shetty, Suchetha Kumari Nalilu, L N Madhu (Journal of Applied Pharmaceutical Science, 2015)
The radioprotective effects of naturally occurring compounds have been investigated in vitro and in vivo considering their pharmacological role in prevention and treatment of cancer. Chitosan (CS) is a naturally occurring polymer that has been increasing attention in pharmaceutical and biomedical applications because of its biocompatibility, biodegradability, nontoxicity, cationic properties and bio adhesive characters. Lymphocytes were treated with different concentrations of chitosan for the period of 2 and 24 hr. Cell viability was determined by tryphan blue dye exclusion assay, single strand DNA damage by alkaline comet assay and in vitro cytogenetic damages were evaluated by micronucleus assays. Treatment of lymphocytes with chitosan before and after the exposure to 4Gy of electron beam radiation (EBR) resulted in the reduction of percentage of tail DNA in comet from 24.06±3.92 to 6.94±1.34 and olive tail moment (OTM) was reduced from 25.34±3.09 to 10.66±0.23 at 10µg/mL concentration. The micronucleus formation in radiation control group (13.75±0.37) was significantly reduced in chitosan pretreated groups 7.63±1.02. Cells treated with chitosan at 10µg/mL showed maximum viability after exposure to EBR. Present investigation data proves the protective effect of CS against EBR induced damage in lymphocyte. However, increase in concentration above 100 µg/mL though resulted in higher protection, an increased cell toxicity was also noticed.
Keywords: Radioprotection, Electron Beam Radiation, Chitosan.